O direito ao grito: a metáfora em A Hora da Estrela, de Clarice Lispector - Dutra, Homero Bergamaschi (My University, 2014)
This essay will try to promote a study about the language used in The Hour of The Star, by Clarice Lispector. A special attention will be given to the use of the metaphor as a way of understanding the many interpretations and significances of the text and how its use collaborates to the cohesion and coherence of the many histories presented in the book. The analysis will have the intelectual suport of the ideas of Martin Heidegger, Paul Ricouer, among other philosophers and scholars and the use of hermeneutics and methaphysics as a form to support this analysis.
O presente ensaio propõe-se a estudar a linguagem de Clarice Lispector na obra A hora da estrela. Atenção especial será dada ao uso da metáfora, visando a compreender as várias interpretações e significações que o texto possui e a verificar de que forma seu uso colabora para a coesão e coerência das diversas histórias dentro do livro. A análise terá o amparo intelectual das idéias de Martin Heidegger e Paul Ricoeur, dentre outros filósofos e estudiosos, e da hermenêutica, como caminho para a interpretação.
Keywords: Letras; Metáfora; Hermenêutica; Metalinguagem; Intertextualidade; Cultura; Clarice Lispector; Metaphor; Hermeneutics; Metalanguage; Intertextuality; Culture